Determinación de la presencia de anticuerpos de Ehrlichia canismediante inmunocromatografìa en perros atendidos en la Clínica Veterinaria Israel de la ciudad de Guayaquil - Samaniego Minetto, César Israel (2025)
Canine Ehrlichiosis is a disease caused by the bacterium Ehrlichia canis family of rickettsiae and transmitted by ticks that affects dogs, causing signs and symptoms such as fever, anemia, lethargy, plateletopenia, epistaxis, hematuria, hind limb paralysis and in severe cases death. ThisresearchwasfocusedondeterminingthepresenceofantibodiesagainstEhrlichia canis in dogs treated at the Israel veterinary clinic in the city of Guayaquil, using the immunochromatography technique, a fast and effective method to detect the presence of antibodies to the disease in blood. Fifty blood samples were collected from dogs with clinical signs compatible with ehrlichiosis and exposure to hematophagous vectors (ticks). The immunochromatographic tests allowed me to identify the presence of specific antibodies with positive and negative results, to evaluate the prevalence of this disease in the canine population studied, indicating active infections and their relationship through a non-parametric type of research, correlating variables such as; age, breed, sex in homogeneous populations. The results obtained from the total of 50 samples tested were as follows: 29 cases representing 58% were positive for the presence of Ehrlichia canis, while 21 cases were negative and represent 42% of the can in the population studied